Diversification of Capabilities of Economies in the Field of Talent Management. Poland Against the Background of the European Union - Sipa, Monika (European Journal of Sustainable Development, 2019)
Among the dilemmas of contemporary enterprises, regions and economies, there is a growing shortage of talent. The demand of the economies and enterprises for specific skills, competences and knowledge that shape their innovativeness and competitiveness is related to the responsible and sustainability human capital management. Attracting and optimizing human capital, which contributes to increasing productivity and prosperity of economies, requires appropriate potential that is built by thought-out and long-term activities within their policies. Therefore, the main objective of the study was to identify changes within the potential of the Polish economy in the context of talent management and to identify areas in which the largest differences are visible in relation to the average of the European Union. The assumptions and data from the Global Talent Competitiveness Index (GTCI) and the European Innovation Scoreboard (EC) were used in the research. The data from the years 2013-2018 were analyzed, with particular focus on skills, on the medium and high level (the output sub-index): Vocational and Technical Skills and Global Knowledge Skills. Key words: EU countries, GTCI, talent management, sustainable development, human capital.